MYPT1, the targeting subunit of smooth-muscle myosin phosphatase, is a substrate for the asparaginyl hydroxylase factor inhibiting hypoxia-inducible factor (FIH). - Webb, J; Murányi, A; Pugh, C; Ratcliffe, P; Coleman, M (2009)
The asparaginyl hydroxylase FIH [factor inhibiting HIF (hypoxia-inducible factor)] was first identified as a protein that inhibits transcriptional activation by HIF, through hydroxylation of an asparagine residue in the CAD (C-terminal activation domain). More recently, several ARD [AR (ankyrin repeat) domain]-containing proteins were identified as FIH substrates using FIH interaction assays. Although the function(s) of these ARD hydroxylations is unclear, expression of the ARD protein Notch1 was shown to compete efficiently with HIF CAD for asparagine hydroxylation and thus to enhance HIF activity. The ARD is a common protein domain with over 300 examples in the human proteome. However, the extent of hydroxylation among ARD proteins, and the ability of other members to compete with HIF-CAD for FIH, is not known. In the present study we assay for asparagine hydroxylation in a bioinformatically predicted FIH substrate, the targeting subunit of myosin phosphatase, MYPT1. Our results confirm hydroxylation both in cultured cells and in endogenous protein purified from animal tissue. We show that the extent of hydroxylation at three sites is dependent on FIH expression level and that hydroxylation is incomplete under basal conditions even in the animal tissue. We also show that expression of MYPT1 enhances HIF-CAD activity in a manner consistent with competition for FIH and that this property extends to other ARD proteins. These results extend the range of FIH substrates and suggest that cross-competition between ARDs and HIF-CAD, and between ARDs themselves, may be extensive and have important effects on hypoxia signalling.